Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Un regard sur la distribution des médecins de famille qui parlent français dans les communautés francophones de l’Ontario - Centre de recherche en santé dans les milieux ruraux et du nord (FOCUS sur la recherche [Université Laurentienne], 2013)

Examining the distribution of French speaking family physicians in Ontario’s Francophone communities - Centre for Rural and Northern Health Research (FOCUS on research [Laurentian University], 2013)

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

L'intervention du gouvernement fédéral canadien en matière de droits linguistiques dans le secteur de la santé - Farley, Roger; Guillemette, Roger; Rivest, François (2015)

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Évaluation des besoins des francophones et des Acadiens de la région de Saint-Jean pour un service de navigation - Forest, Mariève (Réseau santé en français de Terre-Neuve-et-Labrador, 2019)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Énoncé de position commune sur l’offre active des services de santé en français en Ontario - Le Regroupement des Entités de planification des services; de santé en français de l’Ontario; et; L’Alliance des Réseaux ontariens de santé en français (Regroupement des Entités de planification des services de santé en français de l’Ontario et Alliance des Réseaux Ontariens de santé en français, 2015)

Pour un système de santé en français amélioré au Nouveau-Brunswick - Leblanc, Gino (Gouvernement du Nouveau-Brunswick, 2010)

Toward an improved health system in french in New Brunswick - Leblanc, Gino (New-Brunswick Government, 2010)

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau de santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Le Centre de santé de Clare : un modèle pour l'accès à des services de santé en français - Sangaré, Yalla (Reflets, 2014)

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, K; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, L; Pignac, S (2022)

Pratique # 4 : L’intégration de la variable linguistique dans la collecte de données (Île-du-PrinceÉdouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Joint Position Statement on the Active Offer of French Language Health Services in Ontario - The Regroupement des Entités de planification des services; de santé en français de l’Ontario; and; the Alliance des Réseaux ontariens de santé en français (2015)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Promising quantities, disappointing distribution. Investigating the presence of French-speaking physicians in Ontario’s rural francophone communities - Timony, Patrick; Gauthier, Alain; Hogenbirk, John. C.; Wenghofer, Elizabeth (Rural and Remote Health, 2013)
Introduction: Previous studies have suggested that there may be a lack of French language healthcare services in the province of Ontario. The purpose of this study was to determine if physicians in Ontario who expressed a proficiency in providing services in the French language are located in 'Francophone communities'. Method: Responses from 10 968 Ontario-based family physicians (FPs) certified by the College of Family Physicians of Canada and uncertified general practitioners (GPs) who responded to the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey were analysed and compared to the 2006 census of the population of Ontario. Main outcome measures were the number of FP/GPs categorized by their language of competency to conduct medical practice and the number of people categorized by their first official language spoken. The physician-to-population ratio was then compared for different groups of communities in Ontario categorized by the degree of francophonie of the community: strong French communities, with a Francophone population ≥25%; moderate French communities, with a Francophone population of 10-24%; and weak/no French communities, with a Francophone population <10%. Results: There are 5.6 French speaking FP/GPs for every 1000 Francophones in communities with a French population less than 10%. This ratio is considerably greater than what was found in moderate French communities (3.4 FP/GPs) and strong French (1.3 FP/GPs). Overall the lowest ratios were found in rural strong French communities both in southern and northern Ontario (0.8 FP/GPs and 0.9 FP/GPs respectively). The ratio for all of Ontario was 0.7-1.3. Conclusions: As the number of Francophones increases in a community, the availability of French-speaking FP/GPs actually decreases, particularly in rural northern Ontario. Furthermore, there is a paradoxical relationship between the potentially high number of FP/GPs in the province with French-language capabilities and the perceived deficiencies in the availability of French language medical services. Key words: family physician, Francophone community, general practitioners, health and human resources, language, physician-patient ratios, urban. Introduction

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)